(untitled) (European Journal of Behavioral Sciences, 2021)
The purpose of this paper is to determine what motivates generation Z at work. We adopt qualitative research method where we analyze the statements of 317 respondents. Voyant Tools, a web-based text analysis tool is employed. We adopted a three-pronged approach to analyze the data- cyrrus cloud analysis, collocate graph analysis, and principal component analysis represented as scatter plot. The cyrrus cloud analysis revealed the most frequently occurring key words in the corpus- ‘work, ‘people’, ‘job, ‘money’, and ‘learning’. This analysis indicates the most important factors that motivate generation Z. The collocate graph analysis revealed major underlying themes of motivation- ‘work’, ‘job’, and ‘people’ to explain how each of these factors motivate employees. Finally, the principal component analysis explains the interactions between these themes- ‘work’, ‘job’, and ‘people’ to comprehensively explain motivation of generation z workers. Implications for theory and practice are presented.